Forecast of the grain yield based on the trend-state mathematical model - ZHANG Shu-juan; HE Yong (浙江大学学报. 农业与生命科学版)
The trend-state mathematical model has the merits of both simplicity of application and high forecasting precision. It can solve the forecast question of data sequences with trend and heavy random fluctuation. This paper forecasted and analyzed the yield of grain in Zhejiang province by this model. which could provide scientific basis for the planed yield of grain.